A COMPARATIVE STUDIES OF RACIAL PREJUDICE AGAINST AFRICAN-AMERICAN PORTRAYED IN THE HELP AND THE BLIND SIDE MOVIE - ANZANI, MARSYA RISGEA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Keywords: Prejudice, Black African American, Comparative Literature, The Help, The Blind Side movie Literature which uses visual and acoustic elements is movie. Racialprejudice between white and black in this movie continuously appear and becomeinteresting to be studied more. Racial prejudice can happen to anyone, but thewriter here more focus on how the racial prejudice happens to blacks people inAmerica. The writer tries to find the problem of studies about the differences andsimilarities of racial prejudice experienced by two main characters of the moviesThe Help and The Blind Side in 1960 and 2000. The writer uses comparativestudies as the methodology in her research while historical approach is used as aresearch approach. Postcolonialism theory and Cinematography elements are alsoused as a theory to guide the writer study the issue. The writer uses model of prejudice expression who divides by Allport,they are antilocution or spoken abuse, avoidance, discrimination or legalized(Institutionalized) racism, Physical attack or violence against people and property,and extermination or genocide. In the finding of both movies, there are only threemodel of prejudice expression. They are antilocution, avoidance and legalizedracism. Antilocution and avoidance are found in both of the movies, whilelegalized racism is only found in The Help movie. This happens because bothmovies have different time setting. From these differences we can see how racialprejudice still exists between those years. In the result of this research the racialprejudice has decreases in their phase. There is a rule about Black and Whitesegregation in 1960 era that the writer found in The Help movie, but this law doesnot exist anymore in 2000 era as depicted The Blind Side movie because thepeople are more aware about humanism.